Silver(I), gold(I) and palladium(II) complexes of a NHC-pincer ligand with an aminotriazine core: a comparison with pyridyl analogues - Vaughan, Jeffrey; Carter, Damien; Rohl, Andrew; Ogden, Mark; Skelton, B.; Simpson, Peter; Brown, David (2015)
Dinuclear silver, di- and tetra-nuclear gold, and mononuclear palladium complexes with chelating C,N,C diethylaminotriazinyl-bridged bis(NHC) pincer ligands were prepared and characterised. The silver and gold complexes exist in a twisted, helical conformation in both the solution- and the solid state. In contrast, an analogous dinuclear gold complex with pyridyl-bridged NHCs exists in a linear conformation. Computational studies have been performed to rationalise the formation of twisted/helical vs. linear forms.